Analysis of Figurative Language on “Tua Kalok Ceremony” - Maria Fatima (Leksikon: Jurnal Pendidikan Bahasa, Sastra, dan Budaya, 2023)
This research  aims to identify and analyze the meaningof figurative language on tua kalok ceremony.The researcher used qualitative method.  Data collection techniques used in this research used, interview and  documentation.In the results there are  process of tua kalok ceremony,in the process of Tua Kalok Ceremony have three stages are the preparation stage of the ritual, the main stage, and the final stage and the kind of figurative language found in Tua Kalok ceremony is synecdoche,personification and repetition, one of the  meaning on figurative language found in Tua Kalok ceremony is  Synecdoche,example Mai ita tinu Tua Supan widin jajin nan or Let us drink tua and mixed in goat's blood,the meqaning that let us drink tua mixed with goat's blood, which symbolizes taking the traditional oath.